Proceedings of the International Symposium on Performance Science 2007 - Williamon, Aaron; Coimbra, Daniela (Utrecht European Association of Conservatoires (AEC), 2007)
Performance is a multifaceted pursuit, and as such, the study andinvestigation of performance has become increasingly interdisciplinary inrecent years. The International Symposium on Performance Science aims tobring together artists and scientists, researchers and practitioners, andstudents and teachers for a lively exchange on performance and the skillswhich underpin it.The first ISPS, held in Porto?s Casa da Música on 22-23 November 2007,focused on theories, methods, and applications of performance science withinthe field of music. Musical performance, even at its most elementary levels,requires the management of a wide array of cognitive, motor, perceptual, andsocial skills. Together, these enable instrumental and vocal control,interpretive insight, and close coordination and synchrony with fellow performers.These skills, moreover, are influenced by the physical strains ofpracticing and performing, as well as the demands that arise from performingin different venues and in front of different audiences. It seems clear,therefore, that there is tremendous scope for furthering insight into musicmaking by engaging in interdisciplinary discourse and debate; given thediverse nature of musical performance, it also seems clear that the fruits ofsuch discourse will offer far reaching implications for fields beyond music.For ISPS 2007, researchers and practitioners at every level were invited tosubmit papers on work exploring the interface between skilled artistry andscientific discovery. The result is a collection of articles that showcase recentinitiatives which have employed scientific theories and methods to inform theart of performance and used performance as an exemplary means of advancingtheories and applications of science. These proceedings, which reflectthe chronology of the symposium, represent a broad range of applicationsand interests from across the field of music, as well as the natural, social, andapplied sciences.We hope that this volume will spark further discussion within and beyondmusic and, importantly, give rise to subsequent collaborative investigations.We believe that it is through an interdisciplinary approach that research willcontribute most significantly to the understanding of performance and toassist performers in their primary role: performing.